Encyclopedia of associations - Akey, Denise S. (New York : Gale Research Co., 1980)
A comprehensive list of national organizations described briefly, with names, addresses, and telephone numbers. Associations keep track of industry data for their members and may have valuable information on an industry that would not be found in standard business sources. Indexes include name of organization, key word, and geographic area.
v. 1. pt. 1-2. National Organizations of the U.S. -- v. 1. pt. 3. Name and keyword index. -- v. 2. Geographic and executive indexes.
Issued in 2 v., 1961; in 3 v., 1964-83, 1989- ; in 4 v., 1984, 1986-88; in 5 v., 1985.
New associations and projects (varies), issued 4 months after v. 1, lists additional associations not included in v. 1.
Has inter-edition supplements: Updating service, issued twice a year 1985- lists changes to associations listed in v. 1 & 3; International organizations supplement to v. 4 issued annually 1987-88.
Rankings indexes issued with the 21st ed.- to provide ranked listings by membership size, staff size, annual budget, and founding date for organizations listed in v. 1.
Issued online with title: Associations unlimited (subscription required for access).
CD-ROM ed. also available: Gale global access. Association, <Dec. 1990->; Encyclopedia of associations CD-ROM, <Dec. 1992-June 1994>
Keywords: Associations, institutions, etc. -- Directories; Associations, institutions, etc. -- United States -- Directories; Directories; Directories; Directories